In hock : pawning in America from independence through the Great Depression - Woloson, Wendy A., 1964- (University of Chicago Press, 2009)
The definitive history of pawnbroking in the United States from the nation's founding through the Great Depression, this volume demonstrates that the practice was inextricably intertwined with the rise of capitalism. The class of working poor begotten by this economic tide could make ends meet, Wendy Woloson argues, only by regularly visiting pawnshops to supplement their inadequate wages. Nonetheless, businessmen, reformers and cultural critics berated the shops for promoting vice and used anti-Semitic stereotypes to cast their proprietors as greedy and cold-hearted. Parsing and subverting these caricatures, Woloson shows that pawnbrokers were in fact shrewd businessmen, often from humble origins, who honed sophisticated knowledge of a wide range of goods and their values in different markets.